Making the case for a pluralistic approach to intellectual property regulation in developing countries. Issue 1 (February 2016) - Forsyth, Miranda
Abstract : Many of the poorest and least developed countries in the world are currently experiencing pressure to adopt global intellectual property regimes in order to promote their socio-economic development. These regimes are claimed to be necessary to stimulate innovation, creativity and the transfusion of new knowledge. However, international organizations and developing agencies making such claims often overlook the existing local intellectual property systems that exist in many developing countries. These occupy much of the same regulatory space as global intellectual property rights, but are often based on very different value systems and cultural and philosophical underpinnings. The introduction of a global system based on private property rights and the market economy is therefore likely to have significant effects both upon these local regulatory systems and upon the social and economic relations of the society of which they are a part. This paper, which takes as an example the Pacific Islands region, argues that consideration be given to a pluralistic approach to intellectual property regulation, one that involves the creative weaving together of both global and local systems for the production and use of knowledge and innovation.